Dehydration kinetic study of a chemical heat storage material with lithium bromide for a magnesium oxide/water chemical heat pump. (July 2015) - Myagmarjav, Odtsetseg; Ryu, Junichi; Kato, Yukitaka
Abstract: The reaction performance of a novel chemical heat storage composite as thermal energy storage medium were evaluated for use in a magnesium oxide/water chemical heat pump. The composite, called EML, is composed of pure Mg(OH)2 powder and support materials, including LiBr and expanded graphite to improve reactivity and heat transfer, respectively. The heat storage and heat output capacities of the EML composites were evaluated based on laboratory experiments of dehydration and hydration processes for various molar mixing ratios α of LiBr to Mg(OH)2 using the thermogravimetric method. The heat storage and heat output capacity of the EML composites increased with increasing α . The EML composite with α = 0.100 was estimated to be able to store 1.3 times the heat stored in pure Mg(OH)2 powder after 30 min. Based on these evaluations, the EML composites exhibited sufficient heat storage, heat output capacity, and good mold-ability for practical use in a heat exchange reactor. The EML composite was accordingly confirmed as a candidate material for use in chemical heat pumps. Thus, potential use of the EML composite in a magnesium oxide/water chemical heat pump coupled with a small nuclear reactor for district heating systems was evaluated based on the experimental results. Highlights: A composite, called EML, was composed of pure Mg(OH)2, LiBr and expanded graphite. The effects of molar mixing ratios α of LiBr to Mg(OH)2 were investigated. Heat storage (output) capacity of the EML composites increased with increasing α . EML with larger α had higher heat storage (output) capacity than pure Mg(OH)2 . EML could potentially be used as chemical heat storage materials for MgO/H2 O CHPs.